Early changes in cartilage pericellular matrix micromechanobiology portend the onset of post-traumatic osteoarthritis. (15th July 2020) - Chery, Daphney R.; Han, Biao; Li, Qing; Zhou, Ying; Heo, Su-Jin; Kwok, Bryan; Chandrasekaran, Prashant; Wang, Chao; Qin, Ling; Lu, X. Lucas; Kong, Dehan; Enomoto-Iwamoto, Motomi; et al.
Abstract: The pericellular matrix (PCM) of cartilage is a structurally distinctive microdomain surrounding each chondrocyte, and is pivotal to cell homeostasis and cell-matrix interactions in healthy tissue. This study queried if the PCM is the initiation point for disease or a casualty of more widespread matrix degeneration. To address this question, we queried the mechanical properties of the PCM and chondrocyte mechanoresponsivity with the development of post-traumatic osteoarthritis (PTOA). To do so, we integrated Kawamoto's film-assisted cryo-sectioning with immunofluorescence-guided AFM nanomechanical mapping, and quantified the microscale modulus of murine cartilage PCM and further-removed extracellular matrix. Using the destabilization of the medial meniscus (DMM) murine model of PTOA, we show that decreases in PCM micromechanics are apparent as early as 3 days after injury, and that this precedes changes in the bulk ECM properties and overt indications of cartilage damage. We also show that, as a consequence of altered PCM properties, calcium mobilization by chondrocytes in response to mechanical challenge (hypo-osmotic stress) is significantly disrupted. These aberrant changes in chondrocyte micromechanobiology as a consequence of DMM could be partially blocked by early inhibition of PCM remodeling. Collectively, these results suggest that changes in PCM micromechanobiology are leading indicators of the initiation of PTOA, and that disease originates in the cartilage PCM. This insight will direct the development of early detection methods, as well as small molecule-based therapies that can stop early aberrant remodeling in this critical cartilage microdomain to slow or reverse disease progression. Statement of Significance: Post-traumatic osteoarthritis (PTOA) is one prevalent musculoskeletal disease that afflicts young adults, and there are no effective strategies for early detection or intervention. This study identifies that the reduction of cartilage pericellular matrix (PCM) micromodulus is one of the earliest events in the initiation of PTOA, which, in turn, impairs the mechanosensitive activities of chondrocytes, contributing to the vicious loop of cartilage degeneration. Rescuing the integrity of PCM has the potential to restore normal chondrocyte mechanosensitive homeostasis and to prevent further degradation of cartilage. Our findings enable the development of early OA detection methods targeting changes in the PCM, and treatment strategies that can stop early aberrant remodeling in this critical microdomain to slow or reverse disease progression. Graphical Abstract: Image, graphical abstract